Extremely low-dose vigabatrin for West syndrome with tuberous sclerosis - Hino-Fukuyo, Naomi; Sato, Yuko; Kakisaka, Yosuke; Endo, Wakaba; Kubota, Yuki; Kikuchi, Atsuo; Kobayashi, Tomoko; Haginoya, Kazuhiro; Uematsu, Mitsugu; Numata, Yurika; Doi, Hiroshi; Mori, Masato; Osaka, Hitoshi; Kure, Shigeo (Journal of Pediatric Epilepsy, 2013)
Treatment of west syndrome in patients with tuberous sclerosis, the relevant effective period and doses of vigabatrin (VGB) to avoid serious side effects still needs further investigation. We report on a Japanese girl who showed good results with a very low dose of VGB. Tonic spasms appeared at 5 mo of age. Adrenocorticotropic hormone therapy resulted in incomplete seizure control. VGB at the lowest practical dose (30 mg/kg/d) showed complete control after 3 d. With reduction of the dose to 10 mg/kg/d, side effects such as hyperactivity, irritability, and sleep disturbances improved. She was seizure-free for the next 6 mo with an improved developmental quotient. Ophthalmological evaluation revealed no abnormality. The present case illustrates that low-dose VGB therapy (10 mg/kg/d) has fewer side effects and may bring prompt seizure control in west syndrome with tuberous sclerosis.
Keywords: West syndrome; infantile spasms; tuberous screlosis complex; vigabatrin